A REVELAÇÃO DO ABUSO SEXUAL INTRAFAMILIAR INFANTIL: proteção da vítima e responsabilização do agressor - Rafaella de Oliveira Moura; Nabiha de Oliveira Maksoud; Heitor Romero Marques (TRF2, 2020)
This article deals with the disclosure of child sexual abuse when it occurs in the family environment. The study considers the social function of law and interculturality as a line of research, presenting social rights and public policies as a sub-area, based on bibliographic research, of a diagnostic approach. The proposal is to encourage the disclosure of abuse by the child and the procedures to be adopted after this identification. The results show that the underreporting of these cases is related to several subjective factors, which are engendered by the aggressor as a guarantee of hisor herimpunity, therefore there is theneed to transform this veiled condition in which violence is established, with the recognition of the signs manifested by abusedchildren and the mandatory implementation of the discipline of sexual education in public and private schools, as awareness of the victim for hisor herdefense and empowerment in the disclosure, with the subsequent denunciation in the criminal procedure sphere